2021
DOI: 10.3390/ijerph18094442
|View full text |Cite
|
Sign up to set email alerts
|

Psychodrama Group Therapy for Social Issues: A Systematic Review of Controlled Clinical Trials

Abstract: The aim of this study was to carry out a systematic review of controlled clinical trials in order to identify both specific populations and social issues which may benefit from the effective use of psychodrama psychotherapy. A search was conducted in the WoS, SCOPUS, PsychINFO, Medline, Academic Search Ultimate, ProQuest, and PubPsych databases, complemented by a manual search on relevant websites and in the reference lists of the selected studies. Randomized controlled trials (RCTs) and quasi-RCTs of group-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 68 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…Unfortunately, while there are indications of an evolution of psychodrama and applications toward broader fields of research, psychodrama intervention techniques seem to have remained fairly unchanged, save for the online adaptation in Biancalani et al ( 76 )'s paper. Finally, this cluster also showed an increasing focus toward rigorous research and an increased variation in research methodologies, as evidenced by Orkibi and Feniger-Schaal ( 25 )'s integrative review, López-González et al ( 28 )'s systematic review, and Wang et al ( 29 )'s meta-analysis in this cluster, among others (e.g., ( 77 , 87 )). An interesting opinion on research methodology comes from Yaniv ( 86 )'s paper on spontaneity in psychodrama and its relationship with current neurocognitive theories.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Unfortunately, while there are indications of an evolution of psychodrama and applications toward broader fields of research, psychodrama intervention techniques seem to have remained fairly unchanged, save for the online adaptation in Biancalani et al ( 76 )'s paper. Finally, this cluster also showed an increasing focus toward rigorous research and an increased variation in research methodologies, as evidenced by Orkibi and Feniger-Schaal ( 25 )'s integrative review, López-González et al ( 28 )'s systematic review, and Wang et al ( 29 )'s meta-analysis in this cluster, among others (e.g., ( 77 , 87 )). An interesting opinion on research methodology comes from Yaniv ( 86 )'s paper on spontaneity in psychodrama and its relationship with current neurocognitive theories.…”
Section: Discussionmentioning
confidence: 86%
“…While illuminating and providing important insights to modern psychodramatic practices, the paper was not able to survey the history of psychodrama and research trends over its many decades. Recent meta-analyses such as López-González et al ( 28 ) and Wang et al ( 29 ) are also limited in terms of their focus on only controlled clinical trials and the application of psychodrama within the Chinese culture, respectively, without consideration of other methodologies or theoretical papers and a broader cultural context. On the other hand, older systematic reviews have similarly only captured approximately three decades' worth of psychodramatic research ( 14 , 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of the measure of spontaneity benefits psychodrama theory itself since its use may be an opportunity to reinvent it by meeting the new demands coming from the contexts where it is used [18]. On the other hand, in the evaluation of the therapeutic process, the use of the measure of spontaneity may help innovate psychodrama-based interventions [17]. Finally, with the measure now presented, it is possible to correlate spontaneity with creative adaptability in Portuguese-speaking contexts and compare it with other cultural contexts, for example, in the case of the pandemic outbreak of COVID-19 [20,36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, literature in expressive arts in general, and particularly in psychodrama, points out the need for further studies, not only correlational but also randomized clinical trials [16], for which valid psychometric instruments are needed. Finally, several authors [12,17] suggested studies that would bring SAI-R to different cultural contexts. This being said, our work aims to address not only these concerns, making SAI-R a stronger and more valid instrument, but to allow the development of a theoretical model that connects spontaneity and mental health variables [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, literature in expressive arts in general, and particularly in psychodrama, points out the need for further studies, not only correlational but also randomized clinical trials [17], for which valid psychometric instruments are needed. Finally, several authors [13,18] suggested studies that would bring SAI-R to different cultural contexts. This being said, our work aims to address not only these concerns, making SAI-R a stronger and more valid instrument, but to allow the development of the theoretical model that connects spontaneity and mental health variables [19].…”
Section: Introductionmentioning
confidence: 99%